Analisis Pengaruh Strategi Polya dalam Meningkatkan Kemampuan Interpretasi Soal Cerita Matematika Materi Operasi Hitung Campuran pada Siswa Kelas V SD - Erna Sri Mardani; Sahida Nur Arofah; Kowiyah Kowiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the effect of Polya's strategy in improving students' interpretation ability in solving problems contained in story problems on mixed number operations. The method used in this research is a pre-experimental design method with one-group pretest-posttest design type with quantitative research model. The population used in this study were grade V students of SDN X, Lubang Buaya Village, Cipayung District, East Jakarta as many as 13 students. The research data collection technique is using multiple choice questions and essay instruments given to students at the beginning and end of learning. The results showed that there was an influence on students' interpretation ability in solving math story problems on mixed number counting operation material. This is evidenced by the results of the Paired Sample T-test data analysis with a significance value <0.05, which is 0.000 so that H0 is rejected and H1 is accepted. So it can be concluded that there is an influence on the ability to interpret math story problems on mixed number operations using Polya's learning strategy for fifth grade students at SD X.